2003
DOI: 10.1007/s005350300002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Barrett's esophagus in an urban Korean population: a multicenter study

Abstract: The period prevalence of BE among the patients of five referral hospitals was 3.2 per 1000, and it seems that the prevalence of BE in Korean urban area is lower than that in Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
0
26
1
Order By: Relevance
“…One study found that the prevalence of endoscopic CLE in patients with clinical indications was 7.5% [21]. The first multicenter prospective study for LSBE was conducted on 1,553 patients at five referral hospitals in Seoul, and the prevalence of BE was 0.3% [22]. After 2 years, the prevalence of SSBE was assessed prospectively in four referral hospitals of Seoul and the metropolitan areas on 992 patients; CLE was found in 108 patients (10.9%), the overall prevalence of SIM was 3.6%, and only three patients had LSBE [23].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that the prevalence of endoscopic CLE in patients with clinical indications was 7.5% [21]. The first multicenter prospective study for LSBE was conducted on 1,553 patients at five referral hospitals in Seoul, and the prevalence of BE was 0.3% [22]. After 2 years, the prevalence of SSBE was assessed prospectively in four referral hospitals of Seoul and the metropolitan areas on 992 patients; CLE was found in 108 patients (10.9%), the overall prevalence of SIM was 3.6%, and only three patients had LSBE [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Asian countries, long-segment BE is much less prevalent compared to Western countries [11,35]; thus, it has been difficult to understand its characteristics in this geographical area. In Japan, long-segment BE defined by a circumferential length of 3 cm or more is a considerably rare condition, with a reported prevalence as low as 0.2-0.6% [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the established risk factors for BE, such as GE reflux diseases (GERD), hiatal hernia, being an elderly male, and Caucasian race [7], obesity has been frequently identified as a predisposing factor for BE [7,8,9]. However, almost all of the studies on risk factors for BE thus far have originated from Western countries, largely because the incidence of BE, and in particular long-segment BE, is much lower in Asian countries compared to Western countries [10,11]. Since some studies have suggested that the risk factors differ among different ethnic groups [12,13], the risk factors for Asian subjects with BE remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…17 Most Korean patients, however, have been found to have short segment Barrett's epithelium, with long segment Barrett's esophagus being quite rare. 18,19 If a tumor is not detected early, the chance of finding the specialized intestinal metaplasia (SIM) was very low. This may explain why most Barrett's cancers in Korean patients were small sized (less than 20 mm sized) and shallow depth of invasion.…”
mentioning
confidence: 99%